A proposed model for the management of knowledge flows in the international automobile industry supply chain : approaches and methodologies with special reference to DaimlerChrysler and Mercedes-Benz Technology Centre - Le Roux, Pierre (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm)--Stellenbosch University, 2002.